Using Audience Segmentation to Determine Millennial Perceptions toward GM Foods - Katherine Burke Ph.D.; Courtney D Boman Ph.D.; Jeremy D'Angelo; Jason D Ellis Ph.D. (Journal of Applied Communications, 2020)
Millennial consumers are an essential population segment who are currently the third highest spenders in grocery aisles. Millennials are often lumped into one homogenous group; however, they are instead a diverse group comprised of unique characteristics. As producers are increasingly adopting genetically modified (GM) crops, it is essential to understand how consumers perceive the technology. Using the Situational Theory of Publics, an online survey was used to capture character traits of millennials and their perceptions toward GM foods. Using non-probability quota sampling (N=386), millennials were asked to answer demographic questions as well as questions related to their level of support for GM food; their level of involvement in the issue; and their level of knowledge about GM food. Results show that the majority of respondents (77.2%) were not supportive of GM food, and the largest non-supportive category of respondents (25.6%) had high issue involvement but low knowledge about GM food. Of the respondents supportive of GM food, 91% had low issue involvement. By providing insight into millennial characteristics in regards to demographics and where they align in the situational theory of publics, this research can help further risk communication research and improve the understanding of how communication practitioners can strategically communicate with the diverse perceptions and levels of involvement millennials have with GM food.
Keywords: Situational Theory of Publics; Genetically modified food; Millennials; Supportive publics; Non-supportive publics